Fuel wood Collection and Gender Time Poverty: Implications for Development Policy - Jan, Inayatullah; Pervez, Sidra (The Journal of Humanities & Social Sciences, 2023)
The term ‘gender time poverty’ became a buzz word in the development debate after Ester Boserup’s publication ‘Women’s Role in Economic Development’. Since then gender issues are seriously taken into account while formulating a development policy. This study was conducted with the aim to assess the time women spent on fuel wood collection in district Swat, Khyber Pakhtunkhwa, Pakistan. The total sample size for the study was 100 households which were randomly selected from two villages namely Barkaley and Chail. Information from respondents was collected by using semi-structured questionnaire. Descriptive statistics technique was used to analyze the field data. The findings suggest that people in the area were mostly poor and relied on local forest for their domestic energy consumption. Women spent an average six hours per day on fuel wood collection from the nearby woods. Women were intended to spend the same time in income generating activities such as home-based micro-enterprises, knitting and weaving, and poultry farming, etc., if they were provided with any opportunity to save this time. The study concludes that women time poverty is mainly a cause of the excessive fuel wood demand of a household. It is recommended that people in the area should be given access to cost-effective and environment-friendly fuels. Thus the time saved will be used for productive venture which will empower women economically, socially, and politically.